Hepatic and intestine alterations in mice after prolonged exposure to low oral doses of Microcystin-LR. (15th September 2015) - Sedan, Daniela; Laguens, Martín; Copparoni, Guido; Aranda, Jorge Oswaldo; Giannuzzi, Leda; Marra, Carlos Alberto; Andrinolo, Darío
Abstract: Oral intake of Microcystin-LR (MC-LR) is the principal route of exposure to this toxin, with prolonged exposure leading to liver damage of unspecific symptomatology. The aim of the present paper was therefore to investigate the liver and intestine damage generated by prolonged oral exposure to low MC-LR doses (50 and 100 μg MC-LR/kg body weight, administrated every 48 h during a month) in a murine model. We found alterations in TBARS, SOD activity and glutathione content in liver and intestine of mice exposed to both doses of MC-LR. Furthermore, the presence of MC-LR was detected in both organs. We also found hepatic steatosis (3.6 ± 0.6% and 15.3 ± 1.6%) and a decrease in intraepithelial lymphocytes (28.7 ± 5.0% and 44.2 ± 8.7%) in intestine of 50- and 100-μg MC-LR/kg treated animals, respectively. This result could have important implications for mucosal immunity, since intraepithelial lymphocytes are the principal effectors of this system. Our results indicate that prolonged oral exposure at 50 μg MC-LR/kg every 48 h generates significant damage not only in liver but also in intestine. This finding calls for a re-appraisal of the currently accepted NOAEL (No Observed Adverse Effect Level), 40 μg MC-LR/kg body weight, used to derive the guideline value for MC-LR in drinking water. Highlights: MC-LR prolonged oral exposure to low doses generates hepatic steatosis. MC-LR prolonged oral exposure to low doses cause decrease in intestinal intraepithelial lymphocytes. We report MC-LR lowest dose which cause intestinal alterations by oral prolonged exposure. Our results suggest that the NOAEL currently accepted shall be discussed.